Dietary patterns and their associations with the occurrence and severity of early childhood caries among 1–5-year-olds in Iran: A multicenter cluster randomized survey - Ehsan Javadzadeh; Samaneh Razeghi; Ahmadreza Shamshiri; Simin Z. Mohebbi (PLoS ONE, 2025)
Aim A health-promoting and tooth-friendly diet can reduce the risk factors associated with early childhood caries (ECC) and promote overall health in children. This study aimed to identify dietary habits and feeding practices and their associations with ECC among 1–5-year-olds in Iran. Methods This analytical cross-sectional study utilized data from a survey conducted from August 1, 2020, to January 20, 2021. A three-stage stratified cluster sampling method was employed to recruit participants. Parents provided written informed consent in Persian before enrollment and were then interviewed via a valid and reliable questionnaire inquiring about background information, feeding practices, and dietary habits. Each child underwent a dental examination by one of four trained and calibrated dentists to assess dental plaque and ECC. After appropriate weightings were applied, associations between key covariates and outcome measures were analyzed using multivariable logistic regression modeling and multivariate generalized negative binomial regression modeling. Statistical analysis was performed using SPSS V25 and Stata V14.2 software. Results The mean age of the study population was 45.0 (±0.5) months, and 53% (±5%) had ECC. Visible dental plaque was present on the tooth surfaces of 39% ( ± 3%) of the toddlers and 66% ( ± 4%) of the preschoolers. The majority of the children had been breastfed for over 18 months (65%). Most children consumed sugar between meals once a day or less (66%) and fruits once (39%) or twice (37%) a day. ECC experience increased with age and poor oral hygiene across all age groups. Toddlers with a higher frequency of sugar intake between meals had higher dmft and ECC prevalence. The consumption of four to five servings of grain products per day was associated with a five-fold reduction in ECC occurrence (p = 0.047, OR = 0.2). In contrast, the consumption of two servings of fruits per day was associated with a doubling of the dmft score in toddlers (p = 0.015, IRR = 2.0). Conclusions This study identified possible dietary risk factors for ECC in Iranian children, such as increased sugar intake and fruit consumption, while balancing diet with grain consumption played a protective role. Considering the role of oral hygiene and the multifactorial nature of the disease may highlight a route toward developing future targeted and effective preventive strategies.